Upaya Meningkatkan Kinerja Guru dengan Benefit Gaji Dan Tunjangan Kompensasi di KB TKII Al abidin Karanganyar - Amany Hidayah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Objective: This study aims to describe efforts to improve teacher performance through salary benefits and compensation allowances at KB TKII Al Abidin Karanganyar. The research was motivated by the crucial role of teachers as the main agents in improving the quality of education and the need for a fair reward system to enhance their motivation and professionalism. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observations, and document analysis, and were validated using source and method triangulation. The results revealed that the provision of salary benefits and compensation allowances based on objective performance evaluations had a significant positive effect on teacher motivation and professionalism. Various forms of rewards such as salary increases, transportation allowances, “on-time” (TOT) bonuses, and periodic incentives encouraged teachers to be more disciplined, motivated, and committed to improving their teaching competence, particularly in English proficiency. The reward management system implemented at KB TKII Al Abidin Karanganyar proved effective in creating a productive, fair, and Islamic value-based work environment aligned with modern professionalism principles.